(3TQM JUQja GHf GdMGLHs - (3CMeO Hf GdMSf Hf jhSa, aNQ GdOjf GdLGQHQOj , (B746 (3g` s; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s ((3GdfhGLi s)
(3ChdgG (B:s
(3CeG HYO deG cGf cJGH GdJUQja GdPi Ufag GHf GdMGLH eY UZQ MLeI s
(3BNQgG (B:s
(3eYfGgG ai GdZGjI hGdG efgG hGddg CYde Je s
(3GdTGajI ai GdJUQja dGHf GdMGLH GfXQ cTa GdXfhf L(B2 (3U` (B1020s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdUQas